"Acting White": How the Past Implementation of School Desegregation Helped Create Today's Attainment and Achievement Gaps. Issue 4 (1st October 2016) - Buck, Stuart
ABSTRACT: Summarizing my prior work, the only book length treatment of the "acting White" phenomenon (Buck, 2010), I argue that while desegregation was both a moral necessity and a social good, the manner in which desegregation was implemented by White authorities led indirectly to today's achievement gaps. In the course of desegregation previously all-African-American schools were closed, with their faculty and administrators typically demoted or terminated, and their students sent to previously all-White schools, where they were not always welcomed. This massive social change established scholarly achievement as part of a White identity, not a Black identity. Unfortunately, this diagnoses may not lend itself to easy solutions.